2020
DOI: 10.1002/ejoc.202001041
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Carbon–Carbon Bond Forming Reactions with Carbonyls Mediated by Rh–H Complexes

Abstract: Carbon-carbon bond formation is a fundamental transformation of synthetic organic chemistry. This minireview focuses on our works related to reductive aldol reaction, reductive Mannich reaction, reductive α-acylation, and reductive αcarboxylation by using rhodium catalyst to achieve CC bond formation. Rh-catalyzed reductive aldol reaction successfully gave-hydroxy carbonyl compounds from α,-unsaturated carbonyl compounds with aldehydes or ketones by treating with RhCl(PPh 3) 3 and Et 2 Zn. This condition could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…[17][18][19][20] Furthermore, Rh-catalyzed coupling reactions have 3 undergone intense study, and it is even possible to insert a sp 3 carbon (Csp 3 ) into a molecule for the C-C bond formation. [21][22][23][24][25] We also reported an effective formation of a highly reactive rhodium-alkyl complex and its applications to reductive fluoroalkylation, [26,27] α-fluoroalkylation, [28][29][30][31][32] Reformatsky-Honda reaction, [33][34][35][36][37][38][39] reductive α-acylation, [40][41][42] reductive aldol reaction, [43][44][45] and reductive Mannich reaction (Scheme 1). [46,47] Moreover, we reported a new Rh-catalyzed Csp 3 -Csp 3 homo-coupling reaction of benzyl halides, which was concerning a rhodium-bis(benzyl) complex derived from dialkylzinc (R2Zn) and RhCl(PPh3)3 (Scheme 2).…”
Section: Introductionmentioning
confidence: 98%
“…[17][18][19][20] Furthermore, Rh-catalyzed coupling reactions have 3 undergone intense study, and it is even possible to insert a sp 3 carbon (Csp 3 ) into a molecule for the C-C bond formation. [21][22][23][24][25] We also reported an effective formation of a highly reactive rhodium-alkyl complex and its applications to reductive fluoroalkylation, [26,27] α-fluoroalkylation, [28][29][30][31][32] Reformatsky-Honda reaction, [33][34][35][36][37][38][39] reductive α-acylation, [40][41][42] reductive aldol reaction, [43][44][45] and reductive Mannich reaction (Scheme 1). [46,47] Moreover, we reported a new Rh-catalyzed Csp 3 -Csp 3 homo-coupling reaction of benzyl halides, which was concerning a rhodium-bis(benzyl) complex derived from dialkylzinc (R2Zn) and RhCl(PPh3)3 (Scheme 2).…”
Section: Introductionmentioning
confidence: 98%
“…The reductive aldol-type reaction is another important variation that has been reported using metal catalysts such as Co [19][20][21], Cu [22][23][24][25], and others [26][27][28][29][30][31][32] with hydrosilanes (R 3 Si-H) or hydrogen as the reductant. In this area, rhodium catalysis has received significant attention [33][34][35][36][37][38][39][40], and we have also reported reductive α-acylations, reductive aldol-type reactions, and reductive Mannich-type reactions using RhCl(PPh 3 ) 3 with Et 2 Zn [41][42][43][44][45][46][47]. The rhodium-catalyzed reductive aldol reaction of α,β-unsaturated esters with aldehydes or ketones gives aldol-type products in good to excellent yields (Scheme 1) [43,44].…”
Section: Introductionmentioning
confidence: 98%
“…Among all the existing methods, the Staudinger cycloaddition reaction was the first effective approach for the synthesis of β-lactams involving the reaction of diphenylketene with benzylideneaniline, benzaldehyde, and cyclopentadiene, forming [2 + 2] cycloadducts. , Sato et al suggested reductive Mannich reaction of α,β-unsaturated carbonyl compound with imines to give β-lactam as the primary product (Figure a). , Munaretto et al proposed a blue-light-mediated two step reaction of aryldiazoacetates with azides to afford the corresponding imines, which further reacted with aryldiazoacetates to yield corresponding β-lactams (Figure b) . Poteat et al.…”
Section: Introductionmentioning
confidence: 99%
“…25, 26 Sato et al suggested reductive Mannich reaction of α,β-unsaturated carbonyl compound with imines to give β-lactam as the primary product (Figure 2a). 27,28 Munaretto et al proposed a bluelight-mediated 29 two step reaction of aryldiazoacetates with azides to afford the corresponding imines, which further reacted with aryldiazoacetates to yield corresponding β-lactams (Figure 2b). 30 Poteat et al reported α-hydroxylation of sulfonylcyclopropanes to form cyclopropanone, which further undergoes [3 + 1] cycloaddition with hydroxylamines to produce chiral β-lactams (Figure 2c).…”
Section: ■ Introductionmentioning
confidence: 99%